A connectivity modeling and evaluating methodological framework in biodiversity hotspots based on naturalness and linking wilderness. Issue 8 (21st June 2022) - Xu, Bo; Zhang, Yun; Lin, Wenyue
Abstract: Wilderness is important for the maintenance of biodiversity, but human activities are increasingly fragmenting it. This situation has serious impacts on various ecological processes, especially in biodiversity hotspots. In previous studies, connectivity modeling is mostly focused on key species, but this approach is difficult to use in biodiversity hotspots. Therefore, it is more practical to focus on naturalness or wilderness. In this study, the Boolean tool and morphological analysis were used to extract landscape type core as wilderness core and Bridge as structural corridors. Then, connectivity analysis was used to extract the wilderness landscape source (WLS). Linkage mapper and Pinch‐point mapper were used to identify the potential corridors and analyze the Pinch‐Points in the corridor, and network connectivity indexes were used to evaluate the corridor network structure. Finally, wilderness core, WLS, structural corridor, and potential corridor are superimposed to get a wilderness network map. A method framework for comprehensive identification and evaluation of the wilderness network in biodiversity hotspots was proposed. Taking Nujiang Prefecture as an example, a wilderness network was constructed and evaluated based on naturalness and wilderness. The results show that human activity has a clear impact on connectivity and that wilderness networks have the potential to be an efficient alternative to habitat networks. In addition, the method framework has potential applicability to other biodiversity hotspots' regions to reduce the impact of habitat fragmentation on biodiversity. Abstract : In this work, a methodological framework for modeling connectivity of biodiversity hotspots is proposed based on naturalness and linking wilderness. The method has potential applicability to the other biodiversity hotspots regions, which is to reduce the impact of habitat fragmentation on biodiversity.